2005
DOI: 10.1088/0967-3334/26/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Early recognition of regional cardiac ischemia using a 3-axis accelerometer sensor

Abstract: Perioperative mortality in coronary artery bypass grafting is usually caused by reduced left ventricular function due to regional myocardial ischemia or infarction. Post-operative graft occlusion is a well-known problem in coronary surgery. A sensitive tool to detect graft occlusion and monitor myocardial function may give the opportunity to revise malfunctioning grafts before departure from the hospital. This paper describes how a new method can detect cardiac ischemia using a 3-axis piezoelectric acceleromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…The sensor replicated our previously reported results (Elle et al 2005) and gave additional support to the claim that accelerometer data can be used to detect regional cardiac ischemia. There was no biological response to the encapsulation and no damaging of the tissue caused by the shape of the sensor.…”
Section: Animal Experimentssupporting
confidence: 83%
See 1 more Smart Citation
“…The sensor replicated our previously reported results (Elle et al 2005) and gave additional support to the claim that accelerometer data can be used to detect regional cardiac ischemia. There was no biological response to the encapsulation and no damaging of the tissue caused by the shape of the sensor.…”
Section: Animal Experimentssupporting
confidence: 83%
“…In animal experiments we have previously demonstrated that a three-axis accelerometer can be used to detect regional cardiac ischemia (Elle et al 2005). This study used a prototype accelerometer.…”
Section: Introductionmentioning
confidence: 99%
“…In an occluded area, there is a noticeable change to stronger power of higher harmonics of the signal. Early recognition of regional cardiac ischemia is possible through analysis of the accelerometer signal real-time via the fast Fourier_ transform (39). Although the primary application of this device will be in adults vulnerable to cardiac ischemia, it could also have tremendous implications for monitoring of pediatric patients after heart surgery or cardiac transplantation.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…2 By measuring the cardiac motion using a miniaturized 3-axis accelerometer attached to the epicardial surface, previous studies have been able to distinguish between ischemic and normal conditions in pigs as well as humans. [3][4][5] Using an accelerometer to detect cardiac motion abnormalities might therefore prove beneficial when used in the intra-and post-operative phase.…”
Section: Introductionmentioning
confidence: 99%